The Difficulties of Trabeculectomy in a Primary Angle-Closure Glaucoma Patient - Herdina Ramadhani; Nurwasis Nurwasis; Yulia Primitasari; Evelyn Komaratih (Department of Ophthalmology, Faculty of Medicine, Universitas Airlangga, 2022)
Introduction: Trabeculectomy is an incisional surgery for glaucoma patient. Performing trabeculectomy in primary angle-closure glaucoma (PACG) is quite difficult. Caution is needed for the occurrence of flat anterior chamber (FAC) and malignant glaucoma. We present a case management of trabeculectomy in a PACG patient. Case presentation: A 52-year-old male had blurred vision in his left eye since one year ago. The patient felt left visual field narrowing since eight months ago. Patient had type 2 diabetes mellitus. Visual acuity on the left eye was 5/7.5. Intraocular pressure (IOP) increased (29 mmHg). Gonioscopy showed closed angle and peripheral anterior synechiae. Glaucomatous optic neuropathy was found with C/D ratio value of 0.9 and superior-inferior RNFL thinning on optical coherence tomography (OCT). Anterior segment OCT revealed shallow anterior chamber depth (ACD) 2.54 mm. The right eye visual acuity was 5/5, normal IOP, and shallow ACD (2.66 mm). Patient was underwent left eye trabeculectomy. Postoperatively, left eye anterior chamber and bleb were formed. He had normal IOP without glaucoma medications. Conclusions: Trabeculectomy is a surgical procedure for glaucoma. Close monitoring is required to avoid the risk of postoperative FAC and malignant glaucoma in PACG.